Niewydolność serca i płuc, transplantologiaBronchiolitis obliterans syndrome – current prophylaxis and treatment possibilities - Lizak, Maria; Nash, Edward; Chapparro Mutis, Cecilia; Hutcheon, Michael; Zembala, Marian; Keshavjee, Shaf (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Bronchiolitis obliterans syndrome (BOS) treatment remains the „Holy Grail” of lung transplantation. In this article the authors attempt to summarize the results of different immunosuppressive strategies aiming to prevent onset, delay progression and improve prognosis of BOS. Strategies discussed include switching cyclosporine (CSA) to tacrolimus (Tac), azathioprine (AZA) to mycophenolate mofetil (MMF), addition of sirolimus/rapamycin (Sir/Rapa), everolimus, azithromycin (AZI), inhaled steroids, inhaled cyclosporine, cytolytic therapy, photopheresis and total lymphoid irradiation (TLI).